Impact of Trade Openness and Sector Trade on Embodied Greenhouse Gases Emissions and Air Pollutants. (23rd May 2016) - Islam, Moinul; Kanemoto, Keiichiro; Managi, Shunsuke
Summary: The production of goods and services generates greenhouse gases (GHGs) and air pollution both directly and through the activities of the supply chains on which they depend. The analysis of the latter—called embodied emissions—caused by internationally traded goods and services is the subject of this article. We find that trade openness increases embodied emissions in international trade (EET). We also examine the impact of sector trade on EET. By applying a fixed‐effect model using large balanced panel data from 187 countries between 1990 and 2011, we determine that each unit of increase in trade openness results in a 10% to 23% increase in GHGs EET. The sector trade effect is also significant for the embodied emissions of carbon dioxide, methane, nitrous oxide, carbon monoxide, nonmethane volatile organic compounds, particulates and sulfur dioxide. Our findings also clearly indicate that the impact of the gross domestic product (GDP) on the embodied emissions in exports is positive, increasing emissions, but that it is negative on the embodied emissions in imports. We suggest that countries monitor trade sector emissions and trade openness to mitigate global embodied GHG emissions and air pollutants.